Myco-Facilitated Biosynthesis of Nano-Silver From Wasp Nest Fungus, Paecilomyces variotii, and Its Antimicrobial Activity Against MTCC Strains - Nayak, B. K.; Prabhakar, V.; Nanda, Anima (Frontiers in Microbiology, 2022)
The utility of fungi as stabilizing and reducing agents in the biogenic synthesis of silver nanoparticles is striking due to the production of large quantities of biomolecules of minute toxic residuals. During the current study, sunlight- and dark-assessed silver nanoparticles were synthesized from wasp nest fungus, Paecilomyces variotii, at different pHs. Synthesized silver nanoparticles (AgNPs) at 6 pH were found to be more prominent than at 7 and 8 pHs. AgNPs were within the 20- to 90-nm range and were polygonal and elongated in shape. FTIR spectra of light-mediated AgNPs showed diverse transmittance bands than the silver nanoparticles synthesized in the dark. The synthesized AgNPs were found with diverse antimicrobial activities against pathogenic MTCC bacterial strains, i.e., Staphylococcus aureus, Vibrio parahaemolyticus, Escherichia coli, Shewanella putrefaciens, and fungus, Candida albicans. Aqueous filtrate and filtrate-mediated AgNPs combined with methanol solvent extract of yeast extract manitol broth (YEMB) had more inhibitory effects on all bacteria and Candida albicans. Furthermore, the combined effect of AgNPs and methanol solvent extract from YEMB culture filtrate was found more effective against E. coli, while AgNPs combined with methanol solvent of aqueous filtrate had inhibitory effects on E. coli and Candida albicans.